Peningkatan Layanan Kesehatan Karyawan Melalui Sistem Informasi Perlindungan, Pelacakan, dan Pengawasan Covid-19 - Rosalina Rosalina; Genta Sahuri; Simplisius Leandro Okhotan3 (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
During the pandemic, PT. Trendology Indonesia applies the WFH system and implements a work shift system to reduce workplace density. Office and factory space occupancy quotas have been set to limit density and physical contact. PT. Trenologi Indonesia also provides health support to all of its employees by providing medicines or supporting vitamins, routine SWAB Antigen/PCR checks, sharing information regarding locations of vaccination points, and supporting other health systems during the COVID-19 pandemic. In addition, the Human Resources Division must also check employee attendance and employee positions during working hours. However, the process is still carried out by the Human Resources Division manually which causes delays and obstacles. To check and monitor the health conditions of workers so that they can optimally complete their work, one solution is to provide a website that has important features that can be accessed by all workers. So, from the results of this dedication, it will make it easier for the Human Resources (HR) team at partners to collect data for information related to COVID-19 such as vaccination data, health data data, and other information, besides that this system also helps HRD in tracking and monitoring health conditions employees